Introspection into the Guna Wisdom of Ayurveda– A Review From the Clinical Perspective - Mangampadath, Abhilash (International Research Journal of Ayurveda & Yoga, 2022)
The clinical scenario in Ayurveda is currently positioned at a juncture where there is immense demand for standardization and development. Researchers are running after the methods to tackle the issues of individual variations and lack of reproducibility when it comes to the systematic practice of Ayurveda. Under these circumstances, the guna spectrum in Ayurveda, often neglected as a philosophical area that do not have direct clinical applications needs to be revived so that the quintessence of Ayurvedic clinical decision making is translated into the research arena. For this purpose, a thorough analysis of the concepts and their in-depth meaning has to be considered. Also, critical introspection into the current status and its background realities with focus on the systematic narration of Ayurveda is needed like the classification of gunas based upon their clinical importance and therapeutic potentials. This article tries to incorporate this aspect into the science of Ayurveda in light of the clinical and philosophical understanding making it more comprehensive and clinical friendly.